2012
DOI: 10.1002/ajh.23180
|View full text |Cite
|
Sign up to set email alerts
|

Patient adherence to tyrosine kinase inhibitor therapy in chronic myeloid leukemia

Abstract: Dramatically improved survival associated with tyrosine kinase inhibitor (TKI) therapy has transformed the disease model for chronic myeloid leukemia (CML) to one of long-term management, but treatment success is challenged with poor medication adherence. Many risk factors associated with poor adherence can be ameliorated by close monitoring, dose modification, and supportive care. Controlling risk factors for poor adherence in combination with patient education that includes direct communication between the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 18 publications
(28 reference statements)
1
45
0
1
Order By: Relevance
“…25 Variable compliance with long-term therapy, with approximately one-third of patients stopping TKIs altogether, and the development of mutations that provide resistance to TKIs, frequently results in treatment failure, which sometimes leads to accelerated phase or blast crisis. 26,27 Long-term use of TKIs used to suppress leukemia leads to a myriad of side effects, including pleural edema, effusions, pulmonary hypertension, sepsis, gastrointestinal problems, and lethal cardiovascular events. 28,29 Furthermore, outside of stem cell transplantation (SCT), there is no effective therapy of CML in blast crisis or Philadelphia chromosome positive (Ph 1 ) ALL 30 ; treatment with TKIs results in brief responses only.…”
Section: Introductionmentioning
confidence: 99%
“…25 Variable compliance with long-term therapy, with approximately one-third of patients stopping TKIs altogether, and the development of mutations that provide resistance to TKIs, frequently results in treatment failure, which sometimes leads to accelerated phase or blast crisis. 26,27 Long-term use of TKIs used to suppress leukemia leads to a myriad of side effects, including pleural edema, effusions, pulmonary hypertension, sepsis, gastrointestinal problems, and lethal cardiovascular events. 28,29 Furthermore, outside of stem cell transplantation (SCT), there is no effective therapy of CML in blast crisis or Philadelphia chromosome positive (Ph 1 ) ALL 30 ; treatment with TKIs results in brief responses only.…”
Section: Introductionmentioning
confidence: 99%
“…Each assessment tool has advantages and disadvantages that favor or limit their applicability (Pérez-Escamilla et al, 2015). A systematic review of over 6500 citations, with full review of 549 articles published between 1967 and 2001, showed there is no effective approach to assess adherence and that most of the methods used to evaluate adherence in a context of chronic diseases are generally complicated, expensive, and not consistently successful (Jabbour et al, 2012a). Thus, the authors suggest the combination of methods to monitor medication adherence with the purpose of reducing biases and inherent limitations to each instrument.…”
Section: Resultsmentioning
confidence: 99%
“…In this situation, many patients respond to tyrosine kinase inhibitors of second generation such as dasatinib and nilotinib, which are more potent drugs than imatinib and can improve the quality of life of patients with this clinical condition (Jabbour et al, 2012a;Bhamidipati et al, 2013). However, the survival rate of patients with CML adherent to imatinib is 16.9% higher compared to nonadherent patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 From a progressive disease with a poor prognosis, CLM evolved into an illness that permits an adequate quality of life and an overall survival rate greater than 80% at 5 years. 2 Imatinib presents the possibility of a simple, safe, oral, and highly effective outpatient treatment, but at considerable cost.…”
Section: Introductionmentioning
confidence: 99%